REFLEXIONES ACERCA DEL PAPEL DE LAS "EIGNE MEDITATIONEN" PARA LA FORMACIÓN DEL SISTEMA TRANSCENDENTAL DE FICHTE - Serrano Marín, Vicente (Daimon Revista Internacional de Filosofia, 1994)
The article contrasts the trascendental treatment upon wich Fichte attempts to establish theoretical-praxis unity in the bosom of Kant’s philosophy, and the «precritical» nature of Reinhold project, aimed at basing this same philosophy on a principle. After making this distinction, the article considers that Reinhold’s philosophy supposed, in part, a deviation for Fichte’s original project. This deviation, moreover, would be echoed in the treatment, somewhat equivocal, that was given the notion of first principle in Grundlage in 1794. On the contrary, the essay Eigne Meditationen proved to be much more in line with Fichte’s original intention; here, the notion of first principle appears in unquestionably transcendental terms.